The Role of Individual Characteristics, CSR Information, Financial and Non-Financial Compensation to Job Seekers Interests in A Company - Putri Paramita Agritansia; Resa Masela Khairunnisa; Thareq Akbar Adiguna (The Indonesian Journal of Accounting Research, 2017)
Abstract: Human resources are the key to achieving and maintaining corporate goal(s). Obtaining high-quality human resources is a challenging task for every corporation. Therefore, corporations compete in providing attractive compensation packages to both its current and prospective employees. The objective of this study is three folds. Firstly, this study seeks to explore the effect of information on compensation and corporate social responsibility (CSR) disclosures toward fresh-graduate job seekers interests of a company. Next, the objective of this study is to examine the interactional effects between the prior mentioned independent variables. Lastly, this study is conducted to examine the role of moral reasoning as a moderating variable in the relationship between those mentioned above independent and dependent variables. In examining the relationship, this study uses the moderated regression analysis. This study is an experimental study that adopts 2x2 designs amongst subjects. Information on compensation and CSR disclosures are manipulated in this study. The total of thirty-seven people consisted of the final semester undergraduate students and recent bachelor degree graduates participated in this study. In analyzing the collected data, this study uses ANOVA. This study finds that only corporate CSR disclosures affect fresh-graduate job seekers work intention in a corporation. Abstrak: Sumber daya manusia adalah kunci untuk mencapai dan mempertahankan tujuan perusahaan (s). Memperoleh sumber daya manusia berkualitas tinggi adalah tugas yang menantang bagi setiap perusahaan. Oleh karena itu, perusahaan bersaing dalam menyediakan paket kompensasi yang menarik bagi karyawan saat ini dan calon karyawannya. Tujuan dari penelitian ini adalah tiga kali lipat. Pertama, penelitian ini berusaha untuk mengeksplorasi efek informasi tentang kompensasi dan tanggung jawab sosial perusahaan (CSR) pengungkapan terhadap minat pencari kerja fresh-graduate perusahaan. Selanjutnya, tujuan dari penelitian ini adalah untuk menguji efek interaksional antara variabel independen yang disebutkan sebelumnya. Terakhir, penelitian ini dilakukan untuk menguji peran penalaran moral sebagai variabel moderasi dalam hubungan antara yang disebutkan di atas variabel independen dan dependen. Dalam memeriksa hubungan, penelitian ini menggunakan analisis regresi moderat. Penelitian ini merupakan penelitian eksperimental yang mengadopsi desain 2x2 di antara subjek. Informasi tentang kompensasi dan pengungkapan CSR dimanipulasi dalam penelitian ini. Sebanyak tiga puluh tujuh orang terdiri dari mahasiswa sarjana akhir semester dan lulusan gelar sarjana baru berpartisipasi dalam penelitian ini. Dalam menganalisis data yang dikumpulkan, penelitian ini menggunakan ANOVA. Studi ini menemukan bahwa hanya pengungkapan CSR perusahaan yang mempengaruhi niat kerja pencari kerja lulusan baru dalam suatu perusahaan.